Etiopathogenesis of adolescent idiopathic scoliosis (AIS): Role of genetic and environmental factors - Aulia, Teuku N.; Djufri, Djufri; Gatam, Luthfi; Yaman, Aman (Narra Sains Indonesia, 2023)
Adolescent idiopathic scoliosis (AIS) has been known to be related closely to genetic factors. Higher prevalence of AIS among individuals with family history of scoliosis suggesting critical roles of genetic in the pathogenesis of AIS. However, evidence also suggested that environmental factors such as latitude and sun exposure also play a critical role in the pathogenesis of the disease. While genetic factors played an important role in the occurrence of AIS, environmental factors are more likely to affect the progression of the disease. Although the pathogenesis of AIS remains elusive, current knowledge suggests that genetic factors and its interaction with environmental factors are crucial in the development of the disease, explaining differences in clinical characteristics of AIS across the globe. The aim of this review is to summarize the current knowledge of genetic and environmental factors contributing to AIS and their interactions.